2023
DOI: 10.1515/freq-2022-0168
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of novel DGS-loaded low-pass filter with wide stopband

Abstract: This article deals with design and development of a novel 7th order low-pass filter with defected ground structures for S-band applications. The proposed LPF structure was comprised of dumbbell shaped interdigital defected ground structures and open stubs as series inductor and shunt capacitor in the pass band. In addition, an equivalent circuit model was derived and optimized to achieve a 3-dB cut off frequency about 4 GHz with a reflection coefficient of better than −20 dB. Moreover, proposed low-pass filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%